2009
DOI: 10.1002/ar.20902
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Microarchitecture of Murine Colitis‐Associated Lymphoid Angiogenesis

Abstract: In permissive tissues, such as the gut and synovium, chronic inflammation can result in the ectopic development of anatomic structures that resemble lymph nodes. These inflammation-induced structures, termed lymphoid neogenesis or tertiary lymphoid organs, may reflect differential stromal responsiveness to the process of lymphoid neogenesis. To investigate the structural reorganization of the microcirculation involved in colonic lymphoid neogenesis, we studied a murine model of dextran sodium sulfate (DSS)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…The expression of this chemokine has been shown to be elevated within the gut mucosa under conditions of angiogenesis associated with intestinal inflammation [26]. We have not identified gross evidence for inflammation in the intestine of our animals undergoing SBR.…”
Section: Discussionmentioning
confidence: 81%
“…The expression of this chemokine has been shown to be elevated within the gut mucosa under conditions of angiogenesis associated with intestinal inflammation [26]. We have not identified gross evidence for inflammation in the intestine of our animals undergoing SBR.…”
Section: Discussionmentioning
confidence: 81%
“…Various signals are necessary for ectopic lymphoid tissue formation in inflammatory settings [30], but the initiating mechanisms are not understood completely. MIP‐2/CXCL2 is important for recruitment of neutrophils and lymphocytes by gut epithelial cells [18]; in lymphocyte trafficking during autoimmune responses [16]; and for recruitment of lymphocytes to peripheral organs in graft‐ versus ‐host disease [17]; and has been implicated in the neo‐angiogenesis associated with ectopic lymphoid tissue formation [19]. The finding that Cp infection induces lung epithelial cell expression of MIP‐2/CXCL2 and secretion both in vivo and in vitro suggests a mechanism by which both neutrophilia and lymphocytosis may develop and formation of ectopic lymphocyte tissue may be initiated by Cp infection of lung epithelial cells in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…We investigated a link between cytokine production by Cp‐infected lung epithelial cells and inflammation. The chemokine macrophage inflammatory protein (MIP)‐2/CXCL2 recruits both neutrophils and lymphocytes [16–18] and is associated with ectopic lymphoid tissue formation [19]. It has been reported that epithelial cell secretion of MIP‐2/CXCL2 recruits both lymphocytes and neutrophils to the gut [18].…”
Section: Introductionmentioning
confidence: 99%